Los sistemas de innovación y producción en América del Sur: ordenando la heterogeneidad - Ignacio De Angelis (Revista Iberoamericana de Estudios de Desarrollo)
The paper seeks to construct analytical categories based on the study of innovation and production systems to systematize the analysis of the dynamics and processes of technological change in South America. To this end, based on the survey and analysis of a set of input and output indicators, together with the categorization and study of the structure of foreign trade, the article proposes a typology ordered according to the innovation capabilities of each economy, the type of product that guides its international insertion, and the degree of concentration and complexity in technological terms of the export basket.